Loss of Biglycan Enhances Thrombin Generation in Apolipoprotein E-Deficient Mice: Implications for Inflammation and Atherosclerosis. Issue 5 (May 2016) - Grandoch, Maria; Kohlmorgen, Christina; Melchior-Becker, Ariane; Feldmann, Kathrin; Homann, Susanne; Müller, Julia; Kiene, Lena-Sophia; Zeng-Brouwers, Jinyang; Schmitz, Friederike; Nagy, Nadine; Polzin, Amin; Gowert, Nina S.; et al.
Abstract : Objective—: Thrombin signaling promotes atherosclerosis by initiating inflammatory events indirectly through platelet activation and directly via protease-activated receptors. Therefore, endogenous thrombin inhibitors may be relevant modulators of atheroprogression and cardiovascular risk. In addition, endogenous thrombin inhibitors may affect the response to non–vitamin K-dependent oral anticoagulants. Here, the question was addressed whether the small leucine-rich proteoglycan biglycan acts as an endogenous thrombin inhibitor in atherosclerosis through activation of heparin cofactor II. Approach and Results—: Biglycan concentrations were elevated in the plasma of patients with acute coronary syndrome and in male Apolipoprotein E -deficient ( ApoE −/− ) mice. Biglycan was detected in the glycocalyx of capillaries and the subendothelial matrix of arterioles of ApoE −/− mice and in atherosclerotic plaques. Thereby a vascular compartment is provided that may mediate the endothelial and subendothelial activation of heparin cofactor II through biglycan. ApoE and Bgn double-deficient ( ApoE −/− /Bgn −/0 ) mice showed higher activity of circulating thrombin, increased platelet activation and platelet adhesion in vivo, supporting a role of biglycan in balancing thrombin activity. Furthermore, concentrations of circulating cytokines and aortic macrophage content were elevated in ApoE −/− /Bgn −/0 mice, suggesting a proinflammatory phenotype. Elevated platelet activation and macrophage accumulation were reversed by treating ApoE −/− /Bgn −/0 mice with the thrombin inhibitor argatroban. Ultimately, ApoE −/− /Bgn −/0 mice developed aggravated atherosclerosis. Conclusions—: The present results indicate that biglycan plays a previously unappreciated protective role during the progression of atherosclerosis by inhibiting thrombin activity, platelet activation, and finally macrophage-mediated plaque inflammation. Abstract : Supplemental Digital Content is available in the text.